GLUT 4 DI JARINGAN ADIPOSA (GLUT 4 in Adipose Tissue) - Dewi Ratna Sari; Rimbun Rimbun; Tri Hartini Yuliawati; Joni Susanto; Ari Gunawan; Harjanto JM (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
The decreasing of glucose transporter 4 (GLUT 4) in adipose tissue of diabetic and obesity patients are associated withhyperinsulinaemia and insulin resistance. The adipose tissue can be used as therapeutic targets in the treatment of Diabetes Mellitus(DM). Visceral adipose tissue has different morphology and functional with subcutaneous adipose tissue and Vitamin D has been knownto have contributed in DM. The aim of this study is to know the role of cholecalciferol on the expression of GLUT 4 in subcutaneous andvisceral adiposity of diabetic rats by elucidated in those tissues. The subjects of the study consisted of nineteen male diabetic rats of Wistarstrain, which were divided into control group (K) and three (3) treatment groups (X1, X2 and X3). In order to induce the condition ofDM, the animals were fed with high fat diet for three (3) weeks and administered a single intraperitoneal injection of streptozotocin (35mg/kgBW) at the end of the second week. Cholecalciferol were administered with doses of 6.25 μg/kgBW in X1, 12.5 μg/kgBW in X2and 25 μg/kgBW in X3 per oral everyday within 14 days. The subcutaneous and visceral adipose tissues of the subjects were processedinto histological slides with immunohistochemistry staining. The data were analyzed by one way ANOVA test and paired t-test (α= 0.05,significance p<0.05). In this study was found the significance of GLUT 4 expression in subcutaneous adiposity (p=0.035) is differentbetween the groups, the differences were found between group K and groups X1, X2 and X3. Also there were found the significance differentof GLUT 4 expression in subcutaneous adiposities compared with visceral adiposities in all treatment groups (p>0.05). Based on thisstudy it can be concluded that cholecalciferol could increase the expression of GLUT 4 in the subcutaneous adiposity, but not in visceraladiposity of the diabetic rats.